DIGITAL LITERACY BOOST: INTEGRATING ONLINE MAGAZINES FOR SENIOR HIGH SCHOOL IN INDONESIA - Oktaviani, Sri Yuan; Dwiniasih, Dwiniasih; Maisa, Maisa; Chowdhury, Takad Ahmed (Cirebon International Conference on Education and Economics Proceeding, 2024)
The advancement of technology has transformed education by providing numerous online media and resources. This mixed-method research explored the impact of integrating online magazines into the teaching of reading report texts in English for eleventh-grade students at a senior high school in Indonesia. The study assessed how online magazines affect students' reading skills, engagement, and digital literacy. Online magazines were used to address common challenges in reading, such as lack of interest and motivation. Quantitative data were collected from 100 students through a structured questionnaire designed to capture their perceptions and experiences. The findings indicated that online magazines significantly enhanced student engagement and interest. Many students reported feeling more enthusiastic about learning and found online magazines to be enjoyable media. Most students did not find online magazines tedious, and a majority noted that these resources made them more active during learning sessions. Furthermore, a substantial number of students observed improvements in their reading skills and unanimously agreed that online magazines increased their vocabulary. Qualitative data from interviews with ten teachers revealed an increase in students’ willingness to participate in reading activities and an improvement in their comprehension skills. The data suggest that online magazines effectively address reading difficulties by making the learning process more engaging and relevant to students' digital experiences. These findings highlight the potential of online magazines as a valuable educational tool, enhancing reading instruction and fostering positive student responses toward this innovative approach.